2020
DOI: 10.3389/fneur.2020.00917
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Acupuncture in the Treatment of Parkinson's Disease: An Overview of Systematic Reviews

Abstract: Background: The effects of acupuncture on Parkinson's disease (PD) outcomes remain unclear. The aim of this overview was to comprehensively evaluate the methodological quality and applicability of the results of systematic reviews (SRs)/meta-analyses (MAs) that examined the use of acupuncture to treat PD. Methods: Eight databases were searched to retrieve SRs/MAs on the use of acupuncture for the treatment of PD. Two reviewers independently screened and extracted the data usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 55 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…Interestingly, when comparing acupuncture only with medication only, there is no significant difference in the scores. Moreover, evidence-based medicine (EBM) studies have analyzed 13 parallel RCTs and found no difference in the efficacy of acupuncture compared with medication for PD treatment [10], suggesting that acupuncture may achieve an efficacy close to that of medication. The Webster Scale is applied to assess the clinical severity of PD, rating levels of akinesia, rigidity, upper limb swing, gait, tremor, facial appearance, speech, and self-care [16].…”
Section: Clinical Efficacy Of Acupuncture In Parkinson's Disease Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, when comparing acupuncture only with medication only, there is no significant difference in the scores. Moreover, evidence-based medicine (EBM) studies have analyzed 13 parallel RCTs and found no difference in the efficacy of acupuncture compared with medication for PD treatment [10], suggesting that acupuncture may achieve an efficacy close to that of medication. The Webster Scale is applied to assess the clinical severity of PD, rating levels of akinesia, rigidity, upper limb swing, gait, tremor, facial appearance, speech, and self-care [16].…”
Section: Clinical Efficacy Of Acupuncture In Parkinson's Disease Patientsmentioning
confidence: 99%
“…The Webster Scale is applied to assess the clinical severity of PD, rating levels of akinesia, rigidity, upper limb swing, gait, tremor, facial appearance, speech, and self-care [16]. Compared with medication only, acupuncture and medication combined have been shown to result in a greater Webster score reduction, indicating an alleviation of clinical severity [12], and compared with medication only, acupuncture alone similarly exhibited a positive effect for decreasing the Webster score [10], suggesting that acupuncture alone may be able to effectively reduce the severity of PD. EBM reviews reveal that even with an optimized oral dose of L-DOPA, there is a risk for a worsening of movement disorders, and a variety of anti-PD drugs may also induce or exacerbate nonmotor symptoms [17].…”
Section: Clinical Efficacy Of Acupuncture In Parkinson's Disease Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when BEEV is used alone or in combination with conventional drugs for PD, neuronal degeneration is alleviated, and movement disorders are reduced [54]. Several systematic reviews and meta-analyses of RCTs have also been published about the effect and safety of several acupuncture treatment modalities on PD [13,16,17,55]. However, it is unclear which acupuncture modality has a better effect and should be considered in clinical practice and research on PD.…”
Section: Implications For Clinical Practice and Suggestions For Further Researchmentioning
confidence: 99%
“…In South Korea, this can be as high as 76% (9,10). Acupuncture is an essential complementary component to the drug therapy for PD (11). The mechanisms of the effectiveness of acupuncture for the treatment of PD remain uncertain, though an increasing number of studies revealed acupuncture's therapeutic effects both in clinical and animal experiments research for PD (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%